GBI tools for interiors - sustainable planning & management / Rostam Yaman … [et al.] - Yaman, Rostam; Roslan, Rafiudin; Alias, Zarina; Ahmad, Noraini; Adnan, Hamimah (Research Innovation Business Unit, 2014)
The current GBI Assessment Tools in Malaysia are mostly devised to evaluate the environmental impacts of built project without emphasizing more on the impacts of the interior design element aspect on the end user who experience and occupy them. There are two significant reasons; there is no assessment tools specifically designed for an interior design projects. Hence, a new framework for developing GBI assessments criteria and methods are in need to ensure that green and sustainable interiors will reduce environmental impacts while being designeffective and socially responsive. The research is also parallel with the directions set by Malaysian Green Building Confederation (MGBC) and Malaysian Institute of Interior Designers (MIID). In recent MIID Councils Meeting, the agenda in greening the interior project in Malaysia has become one of the main objectives of the Institutions. MIID also has appointed two Council Members collaboratively with MGBC in establishing the GBI criteria and tools for interior project in Malaysia. Besides, the outcome of this research could be highly potential contribution of new GBI rating method for Malaysia. It is also significant and could be replicated for formulating similar indicating frameworks for other countries. The outcome of this research also provides extended theoretical significance to the field of study by filling the gap in GBI assessments framework which specifically addresses an interior design project. The significance of sustainable design in contemporary spaces or interiors is definitely unquestionable in justifying the present environmental plight that the whole humanity and world are confronting now. Designing an interior space with sustainability factors in a piece of mind is an inevitable. Every designer should definitely play a role in moving towards a more sustainable design for future generations. The lack of specifically designated Green Building Management Systems for Interior Design project in Malaysia is the basis of the research.